Analisis Feminisme Liberal terhadap Konsep Pendidikan Perempuan (Studi Komparatif antara Pemikiran Dewi Sartika dan Rahmah El-Yunusiyyah) - Pijar Maulid (Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2022)
Women should get an education like men. This research will explore the concept of women's education of Dewi Sartika and Rahmah El-Yunusiyyah and how the concept of women's education of the two figures relates to liberal feminism. This research is a qualitative research type of library study (library research). This research found that women, according to Dewi Sartika and Rahmah El-Yunusiyyah, must be intelligent, sovereign, and independent. They must be equal and have the same role and responsibility as men in life. The construction of the first two schools specifically for women is one of the proofs that Dewi Sartika and Rahmah El-Yunusiyyah have pioneered gender equality in the world of education for women.